Job: A Christian Sisyphus? Humor and the Triumph o f Humań Experience - Vanhoutte, Kristof K. P. (Stylistyka, 2010)
Over the past decades humor and laughter have come to be accepted as serious topics in academic research and a number of diverse theories on humor and the role of laughter have been developed. These theories, however, consider laughter mainly in its daily aspects or in normal life situations. Starting ffom Albert Camus’ concept of the happy Sisyphus, this paper considers whether the figurę of Job, who seems to inhabit a comparably absurd situation, could also be considered as happy, even laughing. The paper concludes with a distinctive reading of the divine words found at the end of The Book of Job that ma> be fundamental in linking Sisyphus w.th Job.